UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA MELALUI PENERAPAN GENIUS LEARNING PADA MATERI GARIS DAN SUDUT DI KELAS VII MTs ISLAMIYAH MEDAN TAHUN PELAJARAN 2016/2017 - Asrul Asrul (AXIOM : Jurnal Pendidikan dan Matematika, 2017)
This study aims to determine students' mathematics learning outcome in the material Lines and Angles discussion of the relationship between the angle, the position of the two lines, properties and large corner angles in class VII MTs Islamiyah field in the academic year 2016/2017. This research is a classroom action research conducted in 2 cycles including planning, implementation, observation and reflection activities. While to know the student's ability, researchers used the test results of students' individual and group. The subject of this research is the students of class VII-3 MTs Islamiyah Medan which amounted to 22 people consisting of 8 male students and 14 female students. Before giving the action, the percentage of students' classical completeness is seen from the pretest given by the teacher by giving post test of cycle I and post test cycle II with the validated problem. From the results of this class action, the researchers conclude their students' mathematics learning outcome and recommend on implementing learning to teach the material to develop Genius Learning Strategy Learning.